(untitled) (MAUSAM, 1993)
A three-dimensional hydrostatic model has been employed for the study of sea breeze circulations over south West Bengal with special reference to an inland station Kharagpur (22°.21’ N, 87° 19’E). A series of sensitivity experiments have been performed to stress the Importance of differential heating on circulation over south West Bengal during pre-monsoon period. It is found that due to differential heating rate between land and sea surfaces, sea breezes can penetrate to the inland station Kharagpur and beyond even in case of moderate gradient wind. Surface observations at Kharagpur and pilot balloon observation at nearby station Kalaikunda are used to compare the model results. The onset of sea breezes, variation of the air temperature and humidity are In fairly good agreement whereas It over estimates the depth of the circulation and cannot predict the variation of the late morning hours surface wind.